Sustaining the Quality of Telecommunication Services by Using Geographic Information Systems (GIS) (A Field Study on Telecom Egypt-WE) - Hamdy Gomaa Abdel Aziz, Wael Hassan Nabil Mohamed (Design Engineering, 2021)
The Research objective is to identify the effective components of the geographic information systems of the company under study, while determining the extent to which the dimensions of the sustainability of the quality of the telecommunication services of the company under study are available, in addition to analyzing the relationship of the effectiveness of geographical information systems and the sustainability of the quality of the telecommunication services of the company under study, and finally reaching a set of results and recommendations Which is useful in maximizing the benefit from the application of geographic information systems in sustaining the quality of the telecommunication services of the company under study, by selecting the sample of workers in the Egyptian Telecom Company branch in the smart village by (377 singles) at different administrative levels. The research found a statistically significant relationship between digital addressing and the sustainability of the quality of telecommunications services, in addition to a statistically significant relationship between spatial linkage and the sustainability of the quality of telecommunications services, and finally a statistically significant relationship between map production and the sustainability of the quality of telecommunications services.